2022
DOI: 10.3390/ijerph19116403
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Mass Index with Sugar-Sweetened and Dairy Beverages Consumption in Children from the Mexico–USA Border

Abstract: The consumption of sugar-sweetened beverages has been associated with the onset of cardiometabolic diseases. The aim of this study was to describe consumption patterns of sugar-sweetened and dairy beverages and to evaluate their correlation with the body mass index in children residing at the Mexico–USA border. A total of 722 (370 girls, 352 boys) elementary school children aged 9 to 12 years from Tijuana, Mexico, participated in the study. Anthropometric measures were recorded, and a beverage intake questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although the terms free sugar and added sugar are similar, the term free sugar also includes the The association between daily beverage consumption and risk of chronic disease among adult women in Turkey Added sugar intake from beverages, total energy, and carbohydrate intakes were significantly higher in the young women. Gómez-Miranda et al (Gómez-Miranda et al 2022) hypothesised that high consumption of SSB in young adults is in part due to the 'nutrition transition' phenomenon characterized by the consumption of processed foods. These foods are often consumed as fast food meals and are affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the terms free sugar and added sugar are similar, the term free sugar also includes the The association between daily beverage consumption and risk of chronic disease among adult women in Turkey Added sugar intake from beverages, total energy, and carbohydrate intakes were significantly higher in the young women. Gómez-Miranda et al (Gómez-Miranda et al 2022) hypothesised that high consumption of SSB in young adults is in part due to the 'nutrition transition' phenomenon characterized by the consumption of processed foods. These foods are often consumed as fast food meals and are affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported sex differences in BMI [ 43 ] and sugar intake [ 23 , 24 ]; therefore, a sensitivity analysis was conducted to test a possible moderation effect of sex on the association of PCE and TSI with BMI. We also conducted a stratified analysis for boys and girls.…”
Section: Methodsmentioning
confidence: 99%
“…The association between excessive total sugar intake (TSI) and body mass index (BMI) in children and adults has been inconsistent across the literature [ 18 ], with some reports of no association [ 19 ], but with others showing a negative [ 20 ] or a positive association [ 21 , 22 ]. Boys reportedly consume higher amounts of sugar [ 23 , 24 ] and increased total relative energy intake from sugar than girls [ 24 ]. Alterations in reward sensitivity are related to increased dietary sugar intake in children [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, physical inactivity and sedentary behavior are of high public health concern, as there is an interaction between behavioral risk factors that increase risk. For example, the constant exposure to food advertising during television viewing contributes to some extent to the modification of diet behavior, that is, the consumption of unhealthy foods (e.g., processed foods with added sugar) in both children [ 41 ] and adults [ 42 ]. In addition, a lifestyle that reduces NEPA and, thereby, energy expenditure may promote an obesogenic environment; therefore, it was reported that increasing active transportation (e.g., cycling or walking) and reducing automobile use may reduce the prevalence of obesity and NCDs [ 43 ].…”
Section: Promotion Strategiesmentioning
confidence: 99%